Answer:
(4,1)
Step-by-step explanation:
let J(6,6) be x1, y1
let K(2,-4) be x2, y2
midpoint = (x1+x2)/2 , (y1+y2)/2
=(6+2)/2 ,(6-4)/2
= 8/2 ,2/2
=4, 1
Answer:
the difference of 12 and 5 is 7 so it would be 0
Answer:
Step-by-step explanation:
This is a 30°-60°-90° right triangle.
AC is hypotenuse, AB is opposite side to 30° angle.
We know that in such a triangle the side opposite to 30° angle is half the hypotenuse.
<u>So we have:</u>
Step-by-step explanation:
the process is shown in the picture.